Using mobile immunization vans to cover under-served populations in hard-to-reach areas. (30th September 2020) - Siddique, M; Abdullah, S; Siddiqi, D A; Mirza, A; Dharma, V K; Shah, M T; Akhter, M A; Khan, A J; Chandir, S
Abstract: Background: In Pakistan, only 66% of children receive their basic vaccinations. However, the figure masks significant inequalities in vaccine coverage between urban and rural residences, slums and areas distantly located from EPI centers. Frequent outbreaks of vaccine-preventable diseases such as polio and measles, in urban cities like Karachi, signal the need for expanding vaccine services to underserved areas. In Apr'19, we introduced the Mobile Immunization Van initiative in Karachi in collaboration with EPI Sindh. Currently, two vans are deployed in hard-to-reach areas and slums to immunize under-2 children for routine vaccines. Methods: Before the van visit, mobilization efforts are conducted in targeted areas to encourage caretakers to bring their child for vaccination. On the day of visit, the van is parked at a central location, and announcements are played on a loudspeaker to attract caregivers. All vaccinations are administered in the van, and entries are recorded in Government's Digital Immunization Registry along with GIS coordinates of immunized children. The data is then automatically transferred on to a web-dashboard for analysis and tracking. Results: From Apr'19 to Jan'20, the vans have vaccinated 2, 867 children, out of which 50% had never been immunized prior to the van visit. Of those who received their follow-up vaccines from the van, 80% were at least 4 weeks beyond from their vaccine due date. GIS analysis of van data confirmed that immunizations were conducted in slums, and areas distantly located from EPI centers. Moreover, compared to government outreach activity, proportion of BCG, Penta3 and Measles1 administrations in slums was higher through the vans by 5%, 6%, and 4% respectively. Conclusions: The vans provide an opportunity for immunizing never-vaccinated children and children defaulting on their vaccine schedule, from the most vulnerable geographies, while simultaneously enrolling them in the Government's EPI Program for effective tracking. Key messages: The mobile vans help achieve universal immunization coverage through provision of vaccine services in slum and rural hard-to-reach areas with limited access to government-provided services. The mobile vans help vaccinate and capture never-immunized children into the Government's EPI records, reducing the number of children missed through routine services.